-8
2/3(-21/3) + 2/3(-15/3)
-42/9 + -30/9
-72/9 = -8
Answer:
2rcosθ+3rsinθ=6
Step-by-step explanation:
x=rcosθ
y=rsinθ
2rcosθ+3rsinθ=6
Answer:
The answer is
Step-by-step explanation:
Given: f(x) = 3 + 2x - x²
To compute f(3 + h) substitute x = 3 + h.
Similarly, to compute f(h) simply substitute x = h.
We are asked to compute
f(3 + h) = 3 + 2(3 + h) - {(3 + h)²}
= 3 + 6 + 2h - {9 + 6h + h²}
= 9 + 2h - 9 - 6h - h²
= - 4h - h²
Now, f(h) = 3 + 2h - h²
f(3 + h) - f(h) = -4h - h² - 3 - 2h + h²
= -6h - 3
which is the required answer.
Step-by-step explanation:
a) f(1) = -1 → x = -1
b) g(1) = Undefined
c) f(x) = 1 → x= Undefined
d) g(x) = 1 → x= 5